Predictors of Hypoxemia in children (2-60 months) with lower respiratory tract infection - Dr Shikha Malik; Dr Poorva Gohiya; Dr Pragati Sisodia; Dr Lokendra Dave (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Acute lower respiratory tract infection specifically pneumonia, account for considerable number of deaths in under 5 children in our country. Hypoxemia is a dangerous sign which needs to be promptly treated. We have taken up this study in order to point out clinical predictors of hypoxemia so that they can be used at peripheral levels where pulse oxymetry the gold standard for measurement of percent oxygen saturation is unavailable. Materials andMethods: The study was conducted in the pediatric intensive care unit of a medical college over a period of one year. This is a prospective cross sectional study. Children in the age group of 2-60 months were included in the study as per the inclusion criteria. Oxygen saturation of <95% was taken as cut off for hypoxemia.Results: 150 children were studied out of which 35.3% had hypoxemia. Breathlessness, fever, irritability, inability to drink/breast feed, unusual sleepiness, convulsions were the presenting symptoms, out of these fever was present in 84% of children. The most frequent clinical sign was tachypnea (92%), followed by nasal flaring, chest indrawing and crepitations. There were 6 deaths, which were in the hypoxemic group, and no deaths were in the non-hypoxemic group.Conclusion: No single sign is a good predictor of hypoxemia but a combination of signs when used can act as a surrogate for pulse oxymeter. These signs with high positive predictive value can be easily taught to primary health care workers in the peripheral health centers where pulse oxymeters are not available.